2019
DOI: 10.20529/ijme.2018.096
|View full text |Cite
|
Sign up to set email alerts
|

The Medical Termination of Pregnancy Act: Need to keep pace with technology

Abstract: In the summer of 2017, the Supreme Court of India denied permission to abort a 26-week-old foetus, detected with Down syndrome at 22 weeks, to a family which already had a child with special needs, on the grounds that the 20-week mark specified in The Medical Termination of Pregnancy Act of 1971 had been crossed. An Act well formulated and ahead of its time at inception seems not to have kept pace with technology and to be in need of change. We argue that by denying the abortion the Court did not adhere to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Women with emotional difficulties should seek help from counselors, support groups, or mental health specialists trained in reproductive health or post-abortion care. These experts may offer tools, support, and direction in a nonjudgmental manner to assist women in processing their feelings and promoting recovery [33][34][35].…”
Section: Impact On Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…Women with emotional difficulties should seek help from counselors, support groups, or mental health specialists trained in reproductive health or post-abortion care. These experts may offer tools, support, and direction in a nonjudgmental manner to assist women in processing their feelings and promoting recovery [33][34][35].…”
Section: Impact On Womenmentioning
confidence: 99%
“…The choice between misoprostol and gemeprost does not significantly impact the outcomes. However, it should be noted that a multicenter U.S. trial reported a 92% success rate, which might have been influenced by a stringent definition of success (requiring abortion within 15 days after mifepristone administration) and limited prior experience with medical abortion [34].…”
Section: Impact On Womenmentioning
confidence: 99%
“…In 2017, family X. was denied permission to abort a foetus having Down syndrome at 26 weeks of pregnancy, because the 20-week mark had been crossed (13). The family already had a child with special needs, and was not in a position to care for another child with developmental delays and medical problems.…”
Section: Foetus With Down Syndromementioning
confidence: 99%